2021
DOI: 10.3390/ijms222111698
|View full text |Cite
|
Sign up to set email alerts
|

IL-15 Prevents Renal Fibrosis by Inhibiting Collagen Synthesis: A New Pathway in Chronic Kidney Disease?

Abstract: Chronic kidney disease (CKD), secondary to renal fibrogenesis, is a public health burden. The activation of interstitial myofibroblasts and excessive production of extracellular matrix (ECM) proteins are major events leading to end-stage kidney disease. Recently, interleukin-15 (IL-15) has been implicated in fibrosis protection in several organs, with little evidence in the kidney. Since endogenous IL-15 expression decreased in nephrectomized human allografts evolving toward fibrosis and kidneys in the unilate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…The same study reported that IL-15 −/− mice were more susceptible to autoimmune diseases and nephrotoxic serum nephritis. Additionally, IL-15 has been found to counteract renal fibrosis [ 18 ]. In line with these preclinical data, transcriptomic datasets of kidney biopsies from patients with different nephropathies (including IgA nephropathy, segmental and membranous glomerulonephritis) revealed lower IL-15 expression than in healthy controls [ 19 ] and the same results were shown on protein level.…”
Section: Introductionmentioning
confidence: 99%
“…The same study reported that IL-15 −/− mice were more susceptible to autoimmune diseases and nephrotoxic serum nephritis. Additionally, IL-15 has been found to counteract renal fibrosis [ 18 ]. In line with these preclinical data, transcriptomic datasets of kidney biopsies from patients with different nephropathies (including IgA nephropathy, segmental and membranous glomerulonephritis) revealed lower IL-15 expression than in healthy controls [ 19 ] and the same results were shown on protein level.…”
Section: Introductionmentioning
confidence: 99%
“…Chronic kidney disease (CKD) is characterized by the development of renal fibrosis, which is the inevitable consequence of continuous accumulation and activation of myofibroblasts and extracellular matrix deposition in interstitial space leading to organ dysfunction. Fibrosis occurs in every type of CKD, regardless of the cause, and it contributes to a progressive and irreversible loss of renal function (22). It is suggested that pathogenetic mechanisms that lead to the formation of diverticula are similar to the mechanisms that lead to the development of CKD.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, they demonstrated that intrarenal IL-15 is reduced in multiple forms of human chronic kidney disease, that IL-15 significantly inhibited spontaneous EMT in kidney tubular cells, that IL-15 prevented TGF-β1-induced EMT in kidney tubular cells and that IL-15 inhibited TGF-β1-induced activation of Snail expression; a key mediator of profibrotic signaling in EMT [29 ▪▪ ]. Two years later, Devocelle et al expanded upon these findings using an established murine model of chronic kidney disease, unilateral urinary obstruction (UUO) [30 ▪▪ ]. The UUO model is considered a valuable resource for studying the mechanisms of tubular interstitial fibrosis which is recognized as the final common pathway for chronic kidney disease [31–33].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%
“…The UUO model is considered a valuable resource for studying the mechanisms of tubular interstitial fibrosis which is recognized as the final common pathway for chronic kidney disease [31–33]. They found that intrarenal IL-15 and IL-15-IL-15Rα expression were significantly reduced and TGF-β1 was markedly increased in UUO mice, treatment with recombinant IL-15 and IL-15/IL-15Rα-Fc decreased kidney fibrosis in UUO mice and recombinant IL-15 and IL-15/IL-15Rα-Fc reduced myofibroblast expression and release of collagen and fibronectin in UUO mice [30 ▪▪ ].…”
Section: Chronic Kidney Diseasementioning
confidence: 99%